The role of the WISE Consortium in the European DEDIPAC-KH project - Minetto, Marco Alessandro; Ferrari, Emanuela; Ghigo, Ezio; Ghizzoni, Lucia; Lanfranco, Fabio; Lucini, Daniela; Pagani, Massimo; Biolo, Gianni; Di Girolamo, Filippo Giorgio; Portincasa, Piero; et al. (Italian Journal of Anatomy and Embryology, 2017)
WISE (Wellness, nutrItion, Sport and Exercise prevention) is a research consortium including five Italian research teams (University of Turin, University of Milan, University of Trieste, Universiy of Rome “Foro Italico”, University of Bari), operating within the broader framework of the DEDIPAC-KH joint action (Determinants of Diet and Physical Activity Knowledge Hub). Research actions within the WISE consortium, funded by the Italian Ministry of Higher Education & Research, are in line with the main objective of the DEDIPAC-KH of developing an international and interdisciplinary network of researchers on dietary, physical activity and sedentary behaviours, related determinant research and policy interventions. More specifically, the WISE consortium research aimed to contribute to the following task (1.2.4 - Task Leader: Prof. Alan Donnelly): perform SLRs to identify state-of the art methods for physical activity and sedentary behaviour measurements. The focus of task 1.2.4 was to examine the methodological effectiveness (validity, reliability and sensitivity/responsiveness) of measures of physical activity and sedentary behaviours. The approach taken with this task was to examine the methodological effectiveness of measures of physical activity and sedentary behaviours in two populations; i) child/adolescence and ii) adults. Findings on methodological effectiveness of measures of physical activity and sedentary behaviours constitute the basis for a variety of publication and reports, and conference communications. The DEDIPAC-KH project created an unique opportunity for developing a comprehensive analysis on the determinants of diet and physical activity in Italy, and fostered successful collaboration with leading international groups. The findings of the WISE project created valuable information for the implementation of successful policies in Italy.This work was supported by MIUR.